The imperfectionists strategic mindsets for uncertain times - McLean, Robert 1946-; Conn, Charles 1961- (Ascent Audio, 2023)
Consistently effective strategic problem-solving has always been a challenging goal to achieve for leaders. And whether you operate in the business, nonprofit, or policy sector, you've undoubtedly noticed that the problems you face are becoming more complex, multifaceted, and difficult. In The Imperfectionists, a team of veteran executives and strategists deliver an original and compelling examination of what sets exceptional problem solvers apart from the rest of us. In the book, authors Rob McLean and Charles Conn identify six mutually reinforcing approaches that power the problem-solving skills of some of the world's best leaders. From an ever-present curiosity about the problems they face to a high tolerance for ambiguity, the ability to see through multiple lenses, and relentless experimentation, you'll explore the techniques that form the foundation of expert problem-solving mindsets. A powerful argument for the proposition that the world's best problem solvers are made, not born, the book demonstrates the radical and exciting possibilities that arise when leaders embrace imperfection, ambiguity, and experimentation in their daily lives. You'll discover how to crack the code of even the most stubborn and inscrutable problems as you learn to lean into the uncertainty and volatility that define your environment.